Influence of the Level of the Middle River Negro in the Amazon, Brazil, on the Properties of the Blood of the Cururu Freshwater Stingray Potamotrygon wallacei - Adriano Teixeira de Oliveira; Ariany Rabello da Silva Liebl; Maria Fernanda da Silva Gomes; Maiko Willas Soares Ribeiro; Rayana Melo Paixão; Antônia Jaqueline Vitor Paiva; Suelen Miranda dos Santos; João Paulo Ferreira Rufino; Junior Ribeiro Carvalho; Paulo Henrique Rocha Aride (Limnological Review)
Amazonian fishes, as an adaptive form to the annual flood cycle, develop physiological strategies to adjust to variations in their habitats. The results of this study help to understand how freshwater stingrays adapt to changes in river levels and allow us to predict the physiology of blood and water properties in situations of extreme droughts and floods in rivers. This study aimed to evaluate the physiological characteristics of the freshwater stingray Potamotrygon wallacei in response to seasonal variations in the Middle River Negro, analyzing the effects of these changes on its hematological and biochemical parameters and investigating the relationship between these changes and the physicochemical composition of the water. The animals were captured in lakes and marshes in the Mariuá Archipelago in River Negro. Five field collections were carried out during periods of different flood pulses. Blood was collected by puncture of the gill vessel after the animals were anesthetized. Hematological parameters were determined by routine methods for stingrays. Blood parameters reveal close relationships with changes in river levels, which occur throughout a hydrological cycle in the Middle River Negro region. Therefore, this indicates that the hematology of P. wallacei can be used in monitoring, indicating modifications of adverse environmental changes; however, this ecophysiological association is a complex process and needs to be further investigated.